The Impact of KUR Super Mikro on MSME Turnover at Pegadaian Syariah: Dampak KUR Super Mikro terhadap Perputaran Modal Usaha Mikro, Kecil, dan Menengah (UMKM) di Pegadaian Syariah - Muhammad Deffa Ray; Muhammad Syahbudi; Rahmi Syahriza (Universitas Muhammadiyah Sidoarjo, 2025)
General background: MSMEs play a strategic role in driving economic growth and employment absorption in Indonesia. Specific background: However, many MSMEs still face difficulties in accessing formal financing due to high-interest rates and complex requirements, prompting the government to introduce the KUR Super Mikro program through Sharia-based institutions like Pegadaian Syariah. Knowledge gap: Despite its potential, studies analyzing the specific impact of this program on MSME turnover at the branch level remain limited. Aims: This study aims to analyze the impact of the KUR Super Mikro implementation on the turnover of MSMEs at Pegadaian Syariah CPS Ar Hakim. Results: Using a quantitative approach and the Wilcoxon Signed-Rank Test on 78 respondents, the results showed a significant average turnover increase of 79.70% after receiving the financing. Business rotation also improved notably, and all respondents positively assessed the program. Novelty: This study contributes empirical evidence regarding the effectiveness of Sharia-based microfinancing on MSME turnover in a specific Pegadaian branch, which has been rarely studied. Implications: The findings suggest that expanding the KUR Super Mikro program and integrating it with business mentoring is essential to enhance its long-term impact and support MSME sustainability.Highlight : MSME turnover increased by an average of 79.70% after receiving KUR Super Mikro. The speed of business turnover of MSMEs experienced a significant increase. All respondents stated that the program was very helpful for business development. Keywords : KUR Super Micro, MSMEs, Pegadaian Syariah, Turnover, Sharia Financing